Congenital leukemia in Downs Syndrome- A Rare Case Report - Rana, Safia; Jairajpuri, Zeeba Shamim; Garg, Sonia (Bangladesh Journal of Medical Science, 2012)
Congenital leukemia is a rare disorder presenting in the immediate neonatal period & diagnosed at or within few days of birth.1 Because of the doubling time of leukemic cells, the disease becomes clinically evident after birth or shortly thereafter.2 Neonates with Downs syndrome have an increased risk for congenital leukemia particularly acute megakaryoblastic leukemia (FAB M7).3 The incidence of acute megakaryoblastic leukemia in Downs syndrome is estimated to be 400 times than in normal children.4 We present a case of congenital leukemia in a 22 day old female child with Downs syndrome who had cyanosis and skin rashes for 2 days. Diagnosis was established on the basis of hematological investigations and cytochemistry of the cells. DOI: http://dx.doi.org/10.3329/bjms.v11i2.9656 Bangladesh Journal of Medical Science Vol. 11 No. 02 April 2012: 134-136